Rural household typology according to the socio-economic development perspectives - Lorena Florentina Chiṭea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The Romanian rural household is the socio-economic unit for which the agricultural activity continues to be the main source of income or at least of supplementing incomes in the form of self-consumption; thus, most rural households overlap the agricultural household farms/peasant farms/small-sized farms. The actuality of this topic results from the ever increasing importance of small farms in the European Union, the literature highlighting their role in the production of environmental public goods, food security, preservation of traditions and local crafts, being the main driving engine of the rural area, with important role in the demographic, economic and social vitality of the Romanian countryside. The paper intends to establish a typology of the rural households in territorial profile according to the agricultural/non-agricultural employment level, to provide a first information on the degree of rural household dependency on the farming activity. The main working hypothesis is the following: the communities with numerous rural population and lower average age have a higher share of non-agricultural occupations. The methodology used is based on Pearson correlation method that can be positive (in the case of direct correlations) or negative (in the case of inverse correlation) between the avnalyzed variables.
Keywords: R20; Q01; O2; 330; rural area; rural household; rural development